Reprogramming Sovereignty: Financial Algorithms and the Future of Political Economy - Suwan-achariya, Shinasak (National Interest, 2025)
This article examines the epistemological foundations of sovereignty in the context of the declining liberal economic order and the emergence of strategic statecraft. Drawing on Russia’s algorithmic response to Western sanctions, it introduces the concept of sovereign acceleration—a temporal regime enabling strategic outcomes independent of traditional capital accumulation. Utilizing a methodology grounded in strategic epistemology, comparative circuit analysis, and visual infographics, the study argues that new modalities of sovereignty emerge from the capacity to program financial circuits and redesign developmental trajectories beyond the Bretton Woods paradigm. The findings provide a reframing of political economy by integrating resource ontology, financial autonomy, and algorithmic governance into a framework for analyzing sovereign resilience.